Prostacyclin Synthase: Upregulation during Renal Development and in Glomerular Disease as well as Its Constitutive Expression in Cultured Human Mesangial Cells - Thomas Klein; Günther Klaus; Martin Kömhoff (Mediators of Inflammation)
Prostacyclin (PGI2) plays a critical role in nephrogenesis and renal physiology. However, our understanding of how prostacyclin release in the kidney is regulated remains poorly defined. We studied expression of prostacyclin synthase (PGIS) in developing and adult human kidneys, and also in selected pediatric renal diseases. We also examined PGI2 formation in human mesangial cells in vitro. We observed abundant expression of PGIS in the nephrogenic cortex in humans and in situ hybridization revealed an identical pattern in mice. In the normal adult kidney, PGIS-immunoreactive protein and mRNA appear to localize to mesangial fields and endothelial and smooth muscle cells of arteries and peritubular capillaries. In kidney biopsies taken from pediatric patients, enhanced expression of PGIS-immunoreactive protein was noted mainly in endothelial cells of patients with IgA-nephropathy. Cultured human mesangial cells produce primarily PGI2 and prostaglandin E2, followed by prostaglandin F2α Cytokine stimulation increased PGI2 formation 24-fold. Under these conditions expression of PGIS mRNA and protein remained unaltered whereas mRNA for cyclooxygenase-2 was markedly induced. In contrast to its constitutive expression in vitro, renal expression of prostacyclin-synthase appears to be regulated both during development and in glomerular disease. Further research is needed to identify the factors involved in regulation of PGIS-expression.